Production volume of mackarel tuna (Euthynnus affinis) as a one of fisheries commodity in Singkawang City - Sarah Pebiloka; Alfian Johansyah; Lutfi Aggadhania (PAKIS JOURNAL INSTITUTE, 2023)
The purpose of this study was to observe the production volume and production value of mackerel tuna (Euthynnus affinis) during 2018 – 2020 in Singkawang City. Mackerel tuna (Euthynnus affinis) is one of the main fisheries commodities in Singkawang City that is included in the pelagic fish species in the Scombridae family. The capture of this fish species occurs throughout the year which is marked by the volume of production that is always there every month. The production volume of mackerel tuna (Euthynnus affinis) fluctuates every year, both monthly and annually. Where, the value depends on seasonal conditions and is dominantly high during the western and transitional seasons, which is as much as 12% and 13%. Meanwhile, during the western season, mackerel tuna (Euthynnus affinis) production volume is always low with a dominance of 3%. The values range from 2,836 kg – 38,963 kg which is found in August and November. The production value of mackerel tuna (Euthynnus affinis) also follows the pattern of production volume. The production value will be high if the production volume is high. The production value ranges from IDR 66,936,000 – IDR 839,534,000.